p38 MAPK inhibition: A promising therapeutic approach for COVID-19 - Grimes, Joseph M.; Grimes, Kevin V. (Journal of molecular and cellular cardiology, 2020)
COVID-19, caused by the SARS-CoV-2 virus, is a major source of morbidity and mortality due to its inflammatory effects in the lungs and heart. The p38 MAPK pathway plays a crucial role in the release of pro-inflammatory cytokines such as IL-6 and has been implicated in acute lung injury and myocardial dysfunction. The overwhelming inflammatory response in COVID-19 infection may be caused by disproportionately upregulated p38 activity, explained by two mechanisms. First, angiotensin-converting enzyme 2 (ACE2) activity is lost during SARS-CoV-2 viral entry. ACE2 is highly expressed in the lungs and heart and converts Angiotensin II into Angiotensin 1–7. Angiotensin II signals proinflammatory, pro-vasoconstrictive, pro-thrombotic activity through p38 MAPK activation, which is countered by Angiotensin 1–7 downregulation of p38 activity. Loss of ACE2 upon viral entry may tip the balance towards destructive p38 signaling through Angiotensin II. Second, SARS-CoV was previously shown to directly upregulate p38 activity via a viral protein, similar to other RNA respiratory viruses that may hijack p38 activity to promote replication. Given the homology between SARS-CoV and SARS-CoV-2, the latter may employ a similar mechanism. Thus, SARS-CoV-2 may induce overwhelming inflammation by directly activating p38 and downregulating a key inhibitory pathway, while simultaneously taking advantage of p38 activity to replicate. Therapeutic inhibition of p38 could therefore attenuate COVID-19 infection. Interestingly, a prior preclinical study showed protective effects of p38 inhibition in a SARS-CoV mouse model. A number of p38 inhibitors are in the clinical stage and should be considered for clinical trials in serious COVID-19 infection. The p38 MAPK pathway may be disproportionately upregulated in SARS-CoV-2 infection due to loss of ACE2 activity upon viral entry and by direct viral activation of p38 MAPK, a mechanism shown to promote the lifecycle of respiratory viruses including SARS-CoV. Unrestrained p38 MAPK activation results in inflammation, thrombosis, and vasoconstriction, explaining severe cardiac and pulmonary injury in COVID-19. p38 MAPK activation may also facilitate viral entry via ACE2 endocytosis. [Display omitted] •The p38 MAPK pathway is a proinflammatory pathway implicated in lung and heart injury•Loss of ACE2 activity in COVID-19 infection allows for p38 upregulation via Ang II•SARS-CoV-2 may also directly activate p38 via viral proteins to promote replication•Overactive p38 may explain inflammation, thrombosis, and vasoconstriction in COVID-19•p38 inhibitors are in clinical development and could be trialed in COVID-19 patients